Kemampuan Keluarga dalam Merawat Orang dengan Gangguan Jiwa - Sulastri Sulastri (Politeknik Kesehatan Tanjung Karang, 2018)
The dependence level of the patient on the family to fulfill their basic needs was quite high. This was certainly going to interfere with the exercise of family members duties, functions, and responsibilities. This will be disturbed the achievement of the family goals when the family was viewed as a system. This can happen because patients who experience mental disorders were considered as a family burden that can affect the system in the family as a whole. Skills were needed for a family to care patient/person with a mental disorder (ODGJ). Ability to care is a measure of the quality of life ODGJ. This study was to analyze the family ability in caring for patients with mental disorder. This was using a qualitative approach, cross-sectional design. The population was families who have family members with a mental disorder in the work area of Sragi Psychiatric Clinic, South Lampung. Sampling method in this research was purposive sampling and obtained samples of as many as 40 people. Data were taken using questionnaires sheet capabilities of families and were analyzed frequency distribution to measure the ability of the family in caring for psychiatric patients. The analytical test showed that most of the family's ability on the group inadequate. The psychiatric clinic should develop a community mental health nursing programs and make health education or family psychoeducation, as one intervention for families to improve their knowledge and skills in psychiatric treating patients.